Modeling the Managements of the Economies of Developing Countries (Advances in Systems Science and Applications, 2019)
Algorithmization issues of achieving the goals of sustainable development of economies of developing countries of the world are considered. The place of the S. Baizakov’s model system is determined; and that is compared to the FAO models developed for ensuring the productive safety of different countries, as proposed by the World Bank and the OECD management criteria system.